Three Cases of Lymphocytic Infiltration of the Eyelid - Kyoko Sugioka; Akinobu Hayashi; Masako Ichishi; Yasuko Sugimoto; Koji Habe; Keiichi Yamanaka (Dermatopathology, 2021)
Lymphocytic infiltration of the skin (LIS), first reported by Jessner and Kanof in 1953, is a disease of unknown etiology characterized by erythematous papules and plaques on the head, neck, and upper back and histopathological findings of a normal epidermis with underlying lymphocytic infiltration of the reticular dermis without mucin deposition. A 69-year-old man and a 21-year-old woman presented with edematous indurative erythema of the left upper eyelid. Lymphocytic infiltration of the dermis with CD4+ T cell predominance was noted on biopsy. A 68-year-old man presented with a four-year history of recurrent edematous indurative erythema of the right upper eyelid that extended up to the right cheek. Predominantly dermal infiltration of CD8+ T lymphocytes was found on biopsy. We treated all three patients with 8–16 mg of methylprednisolone daily, and the erythema and induration improved. CD4+ T cells were predominant in the acute phase (patients 1 and 2), whereas CD8+ T cells were predominant in the chronic phase (patient 3). CD8+ T cells may be involved in LIS recurrence. Lymphocytic infiltration of the eyelid may be associated with isolated circumscribed, edematous, indurative, colorless lesions that are responsive to daily low-to-middle doses of oral methylprednisolone.